Pre-emptive Censorship of Children’s Literature that is Sexual in Nature by Elementary Librarians in the Middle East - Hajjar, Badria (2021)
Pre-emptive censorship is leading elementary librarians to limit the direct access students should have to certain ideas and information; especially literature that are sexual in nature. This act of censorship raises the issue of the suppressing and manipulation of the educational rights that all students should have when it comes to reading literature that are age appropriate and published specifically for a certain age group. Research has shown that the act of pre-emptive censorship is actually due to internal and external forces that influence and lead to that behavior. Moreover, these internal and external forces may be from within an educational organization such as teachers, librarians themselves, administration or from outside of it such as parents, governments and society. This thesis aims to explore the internal and external forces that influence this act of pre-emptive censorship, specifically for literature that are sexual in nature and within the context of private international schools in the Middle East. Addressing the gap in the literature, this study poses the following two research questions: What are the internal forces that influence the decision of elementary librarians at private schools in the Middle East, when it comes to pre-emptively censoring children’s literature that are sexual in nature? What are the external forces that influence the and lead to that behavior. Moreover, these internal and external forces may be from within an educational organization such as teachers, librarians themselves, administration or from outside of it such as parents, governments and society. This thesis aims to explore the internal and external forces that influence this act of pre-emptive censorship, specifically for literature that are sexual in nature and within the context of private international schools in the Middle East. Addressing the gap in the literature, this study poses the following two research questions: What are the internal forces that influence the decision of elementary librarians at private schools in the Middle East, when it comes to pre-emptively censoring children’s literature that are sexual in nature? What are the external forces that influence the decision of elementary librarians at private schools in the Middle East, when it comes to preemptively censoring children’s literature that are sexual in nature? The above research questions were addressed within the theoretical framework of Kurt Lewin’s (1947) gatekeeping theory and the five levels of analysis associated with it. Furthermore, this study followed a qualitative approach using the exploratory design and involved a semi-structured questionnaire and interviews. Within the context of this study, results for the first research question showed that schools are stronger influencers for the act of pre-emptive censorship compared to personal librarian bias or opinion. Results for the second research question showed that governments, parents and a society’s culture are known to be powerful external forces that enable the act of pre-emptive censorship; where governments and parents received the highest votes among participants. Other than exploring the internal and external forces within the Middle East and being able to rate the forces according to their strengths, an even greater issue was highlighted and reflected towards the end of this study, and it’s the issue of social political power within educational systems. This reflection came as a result of the extent of control and power that external forces have within the Middle East and their control over what children may or may not be allowed exposure to.